Contamination Level of Microbes Isolated From Raw Beef Meat Presearved in a Cash Crunched Nigerian Economy - Amadi-Ikpa C.N.; Aguma I.; Inyang G. E. (MultiTech Publisher, 2023)
The contamination level of microbes isolated from raw beef meat preserved in a cash crunched Nigerian economy was investigated due to spoilage by microbes as observed in the market space. Beef meat samples were purchased from abattoirs, separated and preserved in three parts namely: the salt treated part, the cold/refrigerated treated part and the non-treated part. The meat samples were analyzed using standard microbiological procedure and result showed a significant difference in the microbial load, which were significant in terms of meat spoilage. Thirty-nine microbial isolates were obtained belonging to four species namely: Staphylococcus aureus, Streptococcus faecalis, Escherichia coli and candida sp. Following this, the use of salt as a preservative agent raised the contamination level of the meat. Thus, other forms of preservation should be considered, aimed at cushioning the likelihood of poor Government policies in future, considering the fact that energy supply via electricity is poor.